ANTIBIOTIC PROPHYLAXIS ON ESTOMATOLOGY - Rodríguez Alfaro, Miguel (2004)
Surgical antibiotic prophylaxis consists in the use of an antimicrobial drug in a preventive way, that must be active against microorganisms that in high frequency causes posterior infections of our surgical wounds and maintain effective tissue concentrations along the surgery procedure and the posterior time when appears the bacteremia. To reach a successful treatment is necessary to have the knowledge of the resident bactemial flora and the pathogenous flora that infects our surgical wounds. We must choose the correct antibiotic and use it by the correct time. Generally, that time does not exceed 24 hours and in the prophylactic schemes are used some antimicrobial drugs like beta-lactams, azalides lyncosamides and aminoglycosides, that must be selected depending of the medical condition of the patient and some topic related directly with the surgical technique employed.